Comparison of the effect of autoclaved and non-autoclaved live soil exposure on the mouse immune system - Laura Kummola; Martín I. González-Rodríguez; Pertti Marnila; Noora Nurminen; Tanja Salomaa; Lotta Hiihtola; Iida Mäkelä; Olli H. Laitinen; Heikki Hyöty; Aki Sinkkonen; Ilkka S. Junttila (BMC Immunology, 2023)
Abstract Background . Lack of exposure to the natural microbial diversity of the environment has been linked to dysregulation of the immune system and numerous noncommunicable diseases, such as allergies and autoimmune disorders. Our previous studies suggest that contact with soil material, rich in naturally occurring microbes, could have a beneficial immunoregulatory impact on the immune system in mice and humans. However, differences in the immunomodulatory properties of autoclaved, sterile soil material and non-autoclaved, live soil material have not been compared earlier. Results . In this study, we exposed C57BL/6 mice to autoclaved and live soil powders that had the same rich microbiota before autoclaving. We studied the effect of the soil powders on the mouse immune system by analyzing different immune cell populations, gene expression in the gut, mesenteric lymph nodes and lung, and serum cytokines. Both autoclaved and live soil exposure were associated with changes in the immune system. The exposure to autoclaved soil resulted in higher levels of Rorγt, Inos and Foxp3 expression in the colon. The exposure to live soil was associated with elevated IFN-γ concentration in the serum. In the mesenteric lymph node, exposure to live soil reduced Gata3 and Foxp3 expression, increased the percentage of CD8 + T cells and the expression of activation marker CD80 in XCR1+SIRPα− migratory conventional dendritic cell 1 subset. Conclusions . Our results indicate that exposure to the live and autoclaved soil powders is not toxic for mice. Exposure to live soil powder slightly skews the immune system towards type 1 direction which might be beneficial for inhibiting type 2-related inflammation. Further studies are warranted to quantify the impact of this exposure in experimental type 2 inflammation.